Rancang Bangun Pemetaan UMKM Kota Tegal Berbasis Sistem Informasi Geografis - Noviyanti, Cica; Erawati, Wati; Lesmana, Hendra (Indonesian Journal on Software Engineering (IJSE), 2020)
Abstract: Rapid technological development, the website has become a mandatory media for every agency, company and organization, especially in conveying information to the wider community. MSMEs have an important role in the success of national economic development and are also able to absorb a lower middle class workforce. Likewise, MSMEs in Tegal City, have now become pillars of the economic growth of the people of Tegal City. The City of Tegal MSMEs presents data on the profile of MSMEs that are still conventional and difficult to find, both in location and profile. Geographical Information Systems (GIS) should have been implemented at this time, by utilizing GIS, investors, customers and the wider community will easily get the MSME information. MSME MSMEs Tegal City was designed using the Waterfall method with a Website platform using the PHP programming language and Mysql database. The hope is that this Tegal City SME GIS can become a media of information, promotion to achieve competitiveness in this globalization era.Keywords: Geografis Information System, MSMEs, WaterfallAbstrak: Perkembangan teknologi kian pesat, website sudah menjadi media wajib bagi setiap instansi, perusahaan dan organisasi khususnya dalam menyampaikan informasi kepada masyarakat luas. UMKM mempunyai peranan enting dalam mensukseskan pembangunan ekonomi nasional dan juga mampu menyerap tenaga kerja kelas menengah ke bawah. Begitu pula UMKM di Kota Tegal, kini sudah menjadi pilar pertumbuhan perekonomian masyarakat Kota Tegal. UMKM Kota Tegal penyajian data profil UMKM masih konvensional dan sulit dicari baik lokasi maupun profilnya. Sistem Informasi Geografis (SIG) seharusnya sudah diterapkan saat ini, dengan memanfaatkan SIG maka investor, customer dan masyarakat luas akan mudah mendapatkan informasi UMKM tersebut.. SIG UMKM Kota Tegal dirancang menggunakan metode Waterfall dengan platform Website menggunahakan bahasa pemrogramman PHP dan database Mysql. Harapanya agar SIG UMKM Kota Tegal ini dapat menjadi media informasi, promosi untuk memcapai daya saing di era globalisasi ini.Kata kunci: Sistem Informasi Geografis, UMKM, Waterfall